Vitamin D deficiency and its association with vitamin D receptor gene variants among Malaysian women with hypertensive disorders in pregnancy: protocol for a nutrigenomics study - Ibrahim, Yakubu; Basri, Nurul Iftida; Nordin, Norshariza; Mohd Jamil, Amilia Afzan (JMIR Publications, 2024)
Background: Vitamin D deficiency has been associated with hypertensive disorders in pregnancy (HDP). The risk of developing HDP was reported to be further augmented among individuals with a vitamin D receptor (VDR) genetic variant. However, the reported roles of VDR variants in hypertensive disorders are inconsistent among different populations. Given the relatively higher incidence of vitamin D deficiency among Malaysian pregnant women and the high incidence of HDP in this population, we hypothesize that there may be associations between the risk of vitamin D deficiency and HDP with VDR genetic variants. Objective: This paper outlines the protocol for a study to determine the association of vitamin D status and VDR sequence variants among Malaysian pregnant women with HDP. Methods: This prospective study consists of two phases. The first phase is a cross-sectional study that will entail gathering medical records, a questionnaire survey, and laboratory testing for vitamin D status, with a planned recruitment of 414 pregnant women. The questionnaire will be utilized to assess the risk factors for vitamin D deficiency. The vitamin D status will be obtained from measurement of the vitamin D (25-hydroxyvitamin D3) level in the blood. The second phase is a case-control study involving a Malay ethnic cohort with vitamin D deficiency. Participants will be divided into two groups with and without HDP (n=150 per group). Genomic DNA will be extracted from the peripheral blood monocytes of participants using the Qiagen DNA blood kit, and VDR sequence variants will be determined using polymerase chain reaction-high-resolution melting (PCR-HRM) analysis. Sanger sequencing will then be used to sequence randomly selected samples corresponding to each identified variant to validate our PCR-HRM results. The VDR genotype and mutation frequencies of BsmI, ApaI, TaqI, and FokI will be statistically analyzed to evaluate their relationships with developing HDP. Results: As of December 2023, 340 subjects have been recruited for the phase 1 study, 63% of whom were determined to have vitamin D deficiency. In the phase 2 study, 50 and 22 subjects have been recruited from the control and case groups, respectively. Recruitment is expected to be completed by March 2024 and all analyses should be completed by August 2024. Conclusions: The outcome of the study will identify the nonmodifiable genetic components contributing to developing vitamin D deficiency leading to HDP. This will in turn enable gaining a better understanding of the contribution of genetic variability to the development of HDP, thus providing more evidence for a need of customized vitamin D supplementation during pregnancy according to the individual variability in the response to vitamin D intake.